TRANSIENT STUDY BY THE FINITE ELEMENT METHOD OF THE MECHANICAL BEHAVIOR OF THE CONVENTIONAL NITINOL STENT WITH THE AORTA - Torres, Aristides Rivera; del Pino, Gilberto Garcia; de Almeida Costa, Cleinaldo; Pitta, Guilherme Benjamin Brandão; Dantas, Marcos; da Costa, Ítalo Carvalo (Seven Editora, 2025)
Thoracic aortic aneurysms are a highly serious condition whose consequences can be life-threatening. Despite diagnostic methods and intra- and postoperative monitoring, aneurysms pose a challenge for all involved professionals, especially surgeons. The finite element method is a numerical method that has been used as an innovative approach for safely evaluating stents when implanted and accommodated in the aorta. In this study, a study was conducted using ANSYS Workbench 2022 R2 software to evaluate the mechanical behavior of stents. This study simulated the dynamic response to time-varying loads, using the Transient Structural Analysis tool to calculate displacements, stresses, and deformations over time. DOI: https://doi.org/10.56238/sevened2025.029-054